UTILIZATION OF SRIPOKU.COM ONLINE MEDIA AS A MEDIUM TO MEET THE INFORMATION NEEDS OF JOURNALISM STUDENTS - Muzdalifah Ar'robby (AL-IDZAAH: Jurnal Dakwah dan Komunikasi, 2023)
The human need for various types of information that develops around him is understood as a fact, and this is proof that humans as social beings have an instinctive curiosity. This research will discuss how useful Sripoku.com is as a medium for meeting the information needs of journalism students. This study uses a qualitative method. The technique used in this study is the Random Sampling technique. This research was conducted among journalistic students at UIN Syarif Hidayatullah Jakarta who used Sripoku.com. The data collection technique used by researchers is field research using questionnaires and interviews as research instruments. The purpose of this research is to find out the level of satisfaction of journalistic students with the information presented by online media Sripoku.com and to find out how journalism students use Sripoku.com online media to fulfill their information needs. The research results show that Sripoku.com is considered a very useful and useful source of information for journalism students in supporting their activities in writing articles or news reports.